2007
DOI: 10.1889/1.2798819
|View full text |Cite
|
Sign up to set email alerts
|

Invited Paper: Surface‐emitting‐diode lasers and laser arrays for displays

Abstract: Abstract— High‐power red, green, and blue laser light sources made from vertically emitting arrays of intracavity doubled IR lasers is reported. The emitted infrared light from a monolithic array of large‐aperture vertical cavity lasers is converted into visible light using a PPLN doubling crystal in an external cavity. A volume Bragg grating provides simultaneous feedback for all emitters in the array and sets the laser wavelength. Increased diffraction losses for higher‐order modes result in quasi‐Gaussian b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…This is common practice in electrically-driven semiconductor devices and has been used in particular for devices used for micro-displaytype projection/display applications [103,104]. Recent pulsed pumping experiments [105,106] have shown that this method improves the maximum output power achievable with a given SDL chip as long as the pulse duration is shorter than a few hundred nanoseconds, the typical transient time associated with SDL heating.…”
Section: Power Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is common practice in electrically-driven semiconductor devices and has been used in particular for devices used for micro-displaytype projection/display applications [103,104]. Recent pulsed pumping experiments [105,106] have shown that this method improves the maximum output power achievable with a given SDL chip as long as the pulse duration is shorter than a few hundred nanoseconds, the typical transient time associated with SDL heating.…”
Section: Power Scalingmentioning
confidence: 99%
“…The technological hurdles associated with this are essentially to create a uniformly-pumped 100-to-400 μm-diameter disk and to overcome thermal heating effects. In the main [103,104,150], the latter issue is addressed through the thin-device cooling approach and the use of pulsed pumping. As for the former challenge, two radically different approaches have been proposed to-date (see Fig.…”
Section: Electrically-injected Devicesmentioning
confidence: 99%
“…An integrated OPSL system has been demonstrated by Osram, with wall-plug efficiencies of about 5%. 14,15 Second-harmonic generation of laser-diode emission directly uses either surface-emitting lasers (VCSELs) 16 or edge-emitting laser diodes. The use of VCSELs has advantages for large-volume manufacturing, since surfaceemitting devices allow for wafer-level testing, a straightforward mounting technology, and direct power-scaling by array schemes.…”
Section: Second-harmonic Generationmentioning
confidence: 99%
“…The Arasor laser is described in [19]. Arasor uses frequency doubling for all three colors of its lasers, as shown in Figure 6.…”
Section: Lasersmentioning
confidence: 99%